Handbook of radio and wireless technology - Gibilisco, Stan (McGraw-Hill, 1999)
The book begins with a discussion of fundamental concepts, devices, and systems: EM fields and waves, electronic components, antennas, power supplies, receivers, and transmitters. From there, the topics become more specific, including satellite communication, radionavigation, radiolocation, the INternet, measurement and control systems, privacy, and security. The book concludes with a discussion of personal and hobby communications systems.